EXAMINING THE IMPACT OF ACCESS TO HEALTHCARE INFORMATION IN PROVIDING SERVICE IN HOSPITAL LEVEL OF HORMOZGAN PROVINCE - Zareipour, Parisa; Yazdanpanah, Abbas; Hessam, Somayeh (Universal Journal of Pharmaceutical Research, 2018)
Objective: Examining the impact of access to healthcare information in providing service in hospital level was performed in Hormozgan province. The study is applied in objective respect. Methods: The statistical population of this study includes managers and employees of private hospitals of Hormozgan province who are 3240 persons that based on Morgan sample content table, 380 persons were specified as research sample. The questionnaire has been adjusted based on 5-value Likert scale. For analysis of collected data, Pierson correlation coefficient test using SPSS software version 18 and structural equations approach (pathway analysis) using AMOS software version 20 has examined and tested the research hypotheses. Results: There is a positive and direct relation between access to healthcare information and providing services with correlation coefficient of 0.712. The results structural equation showed that access to healthcare information with pathway factor of 0.82 influences providing service. Conclusion: On the basis of results, with healthcare information it is suggested that topics relating to providing services to be noticed by authorities. Peer Review History: Received 26 March 2018; Revised 4 May; Accepted 12 June; Available online 15 July 2018 Academic Editor: Dr. Iman Muhammad Higazy , National Research Center, Egypt, imane.higazy@hotmail.com Reviewer(s) detail: Dr. Omid Gholami , Sabzevar University of Medical Sciences, Iran, omidghphd@gmail.com Dr. Razan Hani Amin Haddad , Jordan University of Science and Technology, Jordan, razanhh@yahoo.com